Spatial Patterns and Functioning of Water Springs in the Sacred Landscape Structure: The Case of Lviv and Volyn Oblasts of Ukraine - Mishchenko, Olena V.; Petlin, Valerii M.; Puhach, Serhii O. (European Association of Geographers (EUROGEO), 2025)
Sacred springs are significant among water sources, as they serve not only natural functions but also social ones, fulfilling the spiritual needs of residents and pilgrims. This article aimsto determine the spatial distribution and role of consecrated/sacred springs in the formation of sacred landscapes. Sanctified springs act as key components and markers of sacred landscapes. The hydrogeological and climatic conditions of Western Ukraine, particularly in Lviv and Volyn oblasts, contribute to the formation of water springs. These regions' national, ethnological, religious, and cultural characteristics have influenced the development of a network of consecrated/sacred springs. The physio-graphic zoning scheme of Ukraine served as the cartographic basis for this study. During 2018-2023, field research was conducted on 112 sacred springs in Lviv oblast and 61 in Volyn oblast. Also, a survey of residents was carried out to gather information about the history and medicinal properties of the investigated springs. The identified spatial patterns of sacred spring distribution within Lviv and Volyn oblasts indicate that their location, concentration,and functioning depend on the characteristics of the surrounding natural environment. Various types of sacred spring groupings have been recorded, including ribbon, double, dispersed, isolated, compact, and blocked. Sacred/conse-crated springs play a central role in formingsacred landscapes. The adequate functioning of such a landscape requires the development of special organisational, landscape-planning, and protective mechanisms for nature use
Keywords: sacred spring; sacred landscape; Volyn oblast; Lviv oblast; Ukraine